Secretory IgA in the Coordination of Establishment and Maintenance of the Microbiota. Issue 5 (May 2016) - Pabst, Oliver; Cerovic, Vuk; Hornef, Mathias
Abstract : Starting at birth, the intestinal microbiota changes dramatically from a highly individual collection of microorganisms, dominated by comparably few species, to a mature, competitive, and diverse microbial community. Microbial colonization triggers and accompanies the maturation of the mucosal immune system and ultimately results in a mutually beneficial host–microbe interrelation in the healthy host. Here, we discuss the role of secretory immunoglobulin A (SIgA) during the establishment of the infant microbiota and life-long host–microbial homeostasis. We critically review the published literature on how SIgA affects the enteric microbiota and highlight the accessibility of the infant microbiota to therapeutic intervention. Trends: The infant microbiota displays low diversity and high susceptibility to the introduction of new species. With time, diversity increases, leading to a highly competitive and stable community. In the presence of the enteric microbiota, the mucosal immune system matures and the production of high levels of SIgA is induced. Initially provided by breast milk, SIgA is later delivered by receptor-mediated transcytosis at the intestinal epithelium and in bile. A certain fraction of the microbiota displays SIgA coating. Although the mechanisms that determine SIgA coating are not fully understood, it can affect microbial fitness in complex ways that vary with the particular antigen. SIgA stabilizes the microbiota–host interaction. Diversification of memory B cells, rather than permanent activation of naïve B cells, generates plasma cells and contributes to stability in this highly dynamic environment.